Arthroscopic Synovectomy of the Knee Joint in Rheumatoid Arthritis - MATSUI, Nobuo (Japanese Journal of Rheumatism and Joint Surgery, 1989)
Since 1969 we have been conducting arthroscopic synovectomies in treating knee joints with rheumatoid arthritis (RA) . The results have been evaluated on a 3-point scale of good, fair and poor. In our first study, we presented a comparison of the long-term results of arthroscopic punch synovectomy (ps group) and conventional capsulosynovectomy (cs group) . The ps group consisted of 27 cases (41 joints) and the cs group of 17 cases (26 joints) . Both groups exhibited similar aggravation after 8 years but there was less progression of X-ray findings in the ps group. Next we studied 4 5 cases (69 joints) on whom, since July, 1982, arthroscopic synovectomies had been performed using both punch and shaver. As the results for Larsen grade I-II were good in 81.8% of the cases and for Larsen grade III-IV., in 32% of the cases, the results for the early stage cases were clearly superior to those for the late stage cases. In addition, we also set up a grade classification for arthroscopic findings on the cartilage, and have studied the relationship between these arthroscopic findings and postoperative results in regard to 24 cases (38 knee joints) . The degree of cartilage degeneration was classified from 0 to 4 in respect to 6 regions, and our findings were expressed as the median grade of each region. The results for joints with a median grade of 0-2 were judged to be good in 82.1% of the cases, while those with median grade of 3-4 were judged so in 33.3 %. As the results were clearly more favorable in cases with a slight degree of cartilage change, it was concluded that it is important to conduct arthroscopic synovectomy at as early a stage as possible.